Role of jewellery design process in evolving economic consideration / Hema Zulaika Hashim ... [et al.] - Hashim, Hema Zulaika; Abd. Rahman, Khairul Aidil Azlin; Alii, Hassan; Raja Effendi, Raja Ahmad Azmeer; Mohd Yatim, Zailiya (Division of Research and Industry Linkages, 2017)
As eyes are the window to one's soul, design is the expression o f one's desire. The role o f jewellery design process in an evolving economic consideration pronounces that what is affordable in the jewellery design as an end product should be acceptable to the masses, As overall living costs escalate, sustainability and continuity of one’s livelihood must be taken into serious consideration. With reference to the jewellery industry where design is the ultimate differentiator, many studies have been conducted on types of jewellery. Albeit studies tend to be fragmented and focuses on a few stages of the jewellery design process at this point; issue prior to the production is will the design adhere to the economics of production which in return provides added value to the owner? Although the studies are mainly concentrated in the manner of the viewpoints of design and economic,there are still many factors of this concept which remains ambiguous, predominantly in Malaysia. Design-based economy is an idealogy when appropriately impefemented should provide new opportunities in creating economic value, growth, profitability and job opportunities for a healthy business presence and continuation. Design process of an adornment should adhere to the acquiring capability of consumers’ reality. Designers are paving ways to deliver good designs which translates into tangible economical value to each customer. As much as a thing o f beauty, the material (gold) is a form of collateral and contingency plan in many households. The proposed framework was developed on the basis of interview results from the retail jewellery industry in Malaysia. This research shall provide insights into the importance of the role of jewellery design process in Malaysia’s evolving economic climate.